PENGARUH PERSEPSI, MOTIVASI, DAN PENGETAHUAN AKUNTANSI SYARIAH TERHADAP MINAT BERKARIER DILEMBAGA KEUANGAN SYARIAH (Studi Kasus Mahasiswa Jurusan Akuntansi Yang Menempuh Mata Kuliah Akuntansi Syariah) - Nor Maula Annisa; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Perception is the process of individual treatment related to the response, meaning, description, or interpretation of what is felt and what is seen by the five senses in the form of attitudes, opinions and behavior, often referred to as individual behavior. lead to the emergence, direction, and persistence of voluntary activities directed towards certain goals. Sharia accounting is an accounting process based on sharia principles, both in the accounting and recording cycles. An accounting process for sharia transactions. Each institution in Islamic financial institutions aims to help achieve the socio-economic goals of Islamic society. The structure of the Islamic financial institution system in Indonesia consists of bank financial institutions and non-bank financial institutions.Keywords: Perception, Motivation, Knowledge Of Islamic Accounting, Islamic Financial Institutions